Sosialisasi : Perempuan Dan Tindak Pidana Kekerasan Seksual (Immawati Avicenna - Pimpinan Cabang Nasyiatul Aisyiyah Solo Utara): Sosialisasi, Tindak Pidana, Kekerasan Seksual, Perempuan - Kurnianingsih, Marisa; Kuswardani; Pamuncak, Aristya Windiana; Purnamasari, Andi Intan (Jurnal Abdimas Multidisiplin, 2023)
Sexual Violence is an action or act that deviates and violates Human Rights. In this case, women are always the object of criminal acts of sexual violence. Considering that at any time the phenomenon of the occurrence of this crime of sexual violence still exists, in order to realize an effort to prevent and overcome sexual violence by advocating, it is necessary to hold a community service with the theme of discussing the importance of knowledge about criminal acts of sexual violence that continue to occur with the main victims being Woman. The method used in this activity was socialization carried out by the Faculty of Law UMS with North Solo PCNA. The main objective of this socialization is that participants can prevent and overcome criminal acts of sexual violence to advocate for victims in the future.